Telovelar Approach to IVth Ventricle Tumor: Experience and Review of Literature - Roka, Yam B (Nepal Journal of Neuroscience, 2017)
Posterior fossa tumor surgery is challenging especially those located in the deeper regions of the middle and upper part of fourth ventricle. The traditional approach has been the vermis splitting or transcerebellar approach to gain access to these lesions. This is a retrospective study of all the cases operated via the telovelar approach between March 2008 and June 2017 in this centre. A total of eight cases were operated in this study period. With regards to medulloblastoma near total excision was achieved in 50% of the cases and one with total removal. Of these two cases needed postoperative ventriculo-peritoneal shunt , there were two cases of recurrence and in spite of cranio-spinal irradiation there were two deaths. Haemangioblastoma and choroid plexus papilloma were removed in total with no recurrence. One case of ependymoma had excessive bleeding with introperative hypotension leading to abandonment of the procedure. The telovelar approach has been described in detail by various authors elaborating the salient features along with the techniques to access the region around the fourth ventricle without the transvermian approach. The advantages of this approach are the avoidance of splitting the vermis and the theoretical reduced possibility of cerebellar mutism. Excision via bilateral telovelar approach have also been described for large tumors. Nepal Journal of Neuroscience, Vol. 14, No. 2, 2017 Page: 16-20